Forage sources in diets for dairy goats (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to evaluate the use of sorghum silage, Buffel grass hay and forage palm fodder in the diet of dairy goats by means of performance tests and economic viability of different roughage sources. Eight Anglo-Nubian goats, multiparous, weighing around 40.13 ± 2.76 kg of live weight were used. The experiment lasted 84 days, consisting of four periods of 21 days, distributed in two Latin squares (4x4). The treatments represented by diets with different volumetric sources: SSCF: (sorghum silage+ forage palm+ concentrate); BHCF: (Buffel grass hay + cactus forage+ concentrate); SS: (sorghum silage+ concentrate) and BH: (Buffel grass hay + concentrate). Nutritional intake, digestibility, feed behavior, milk production and chemical composition and economic analysis were evaluated. Animals fed the BHCF diet had higher nutrient intakes and consequently were more productive in fat, protein, lactose, fat free solids and total solids. The BHCF diet led to a higher gross income in Brazilian currency. The safety margin of the SSCF diet presented the highest percentage, with 43.06%, and the BHCF diet, the lowest percentage, of 14.89. The association of forage palm with sorghum silage and Buffel grass hay can be used as a bulky source in lactating goat diets.